Development of Website-Based Learning Media to Increase Students' Motivation to Learn Fiqh at SDIT Almawaddah Warrahmah Kolaka - Yuyun Albiya Abidin; Abdul Haris Nasution; Muh. Iqbal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research aims to develop website-based learning media to improve student learning motivation in Fiqh (Islamic jurisprudence) at the Almawaddah Warrahmah Integrated Islamic Elementary School (SDIT) in Kolaka. This research is motivated by the relatively monotonous Fiqh learning process, the limited use of learning media, and low student motivation. Therefore, innovative learning media that is engaging, interactive, and in line with technological developments are needed. This study used the Research and Development (R&D) method with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects were students in grades I, II, and III at SDIT Almawaddah Warrahmah Kolaka. Data collection techniques were carried out through observation, interviews, questionnaires, and learning outcome tests. Data were analyzed using quantitative and qualitative descriptive analysis to determine the level of validity, practicality, and effectiveness of the developed media. The results of the study indicate that the developed website-based learning media is valid and suitable for use based on expert validation. Furthermore, the use of this media has been proven effective in increasing student motivation and learning outcomes, as indicated by an increase in the average score from 68 before use to 85 after use. Thus, website-based learning media can create a more engaging and interactive learning process and increase student motivation in Fiqh learning.